RFID Based Security for Exam Paper Leakage System - Sirisha, Mamilla; Syamala, Neelam (International Journal of Engineering and Technology, 2018)
The examination may be the heart of the education framework. The principal reason for the examination will be to select the proficient applicants for several positions. Every year we get the news regarding postponed/canceled exam because of paper leakages. So we need come up with manageable and compact result and decided to design and execute an â€œexamination paper leakage security framework â€œthat will be a much-protected framework depend on â€œARM processorâ€. Together with â€œthe GSM modem, keypad, electromagnetic lock, and RFID module â€œwould be utilized in this framework. First, the university will send the exam paper to the college in â€œan electronic sealed boxâ€that is termed as â€œElectronic Control Boxâ€. The â€œElectronic Control Box â€œwill be an embedded framework, which might have been proposed utilizing â€œARM processorâ€ that has inbuilt RTC to display â€œthe Electronic Control Boxâ€. Whether anybody tries to open that box previous and afterward the time duration of the RFID swipe, the framework communicates to the university powers by sending â€œand SMS (Short Message Service)â€ through the GSM, which several malfunctioning has taken place with â€œthe Electronic Control Box". For instance, whether the secret key doesnâ€™t match then the client who has access to get the message on his telephone. If we enter the invalid secret ID then the ringer will be ON. Therefore we might effectively recognize that the question papers have been leaked.This paper defines the electronic security for the leakage of question paper that will be an exceptionally protected framework. The examination will be the heart of â€œthe education frameworkâ€. We have recommended an electronic framework to identify and avoid the leakage of exam papers. In this proposed system, the exam papers that are in â€œthe electronically locked boxâ€ will be sent to the examination centers. The box will be unlocked after a predefined time, date and only by a certified client. Essentially the exam papers will be existing in the sub-boxes. Secret ID secures these boxes; the exam manager will send an SMS with the password to open the specific sub-boxes. The electromagnetic lock is used to unlock the box, when the time, date, and password match. In this framework, we are utilizing a ringer for any unapproved interference.Â